Angiopoietins as biomarker of disease activity and response to therapy in multiple myeloma. Issue 7 (July 2013) - Bhaskar, Archana; Gupta, Ritu; Vishnubhatla, Sreenivas; Kumar, Lalit; Sharma, Atul; Sharma, Mehar Chand; Das, Prasenjit; Thakur, Sonu Chand
Abstract: Tumor angiogenesis is a complex process involving interplay of several angiogenic regulators. In the present study, mRNA expression and circulating levels of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), angiopoietin-1 (Ang-1), angiopoietin-2 (Ang-2), hypoxia inducible factor (HiF)-1α, circulating endothelial progenitor cells (cEPCs) and bone marrow microvessel density (MVD) were evaluated in multiple myeloma (MM). Compared to healthy controls, the levels of VEGF, bFGF, Ang-2, HiF-1α and cEPCs were significantly higher and Ang-1 and Ang-1/Ang-2 were lower in MM ( p < 0.01). cEPC numbers correlated with Ang-1 ( p = 0.03), Ang-2 ( p = 0.01) and VEGF ( p = 0.002). On multivariate analysis, reduced Ang-1/Ang-2 ratio ( p = 0.005) at baseline was an independent predictor for response to therapy. After therapy, a decrease in Ang-2 ( p < 0.001) and an increase in Ang-1/Ang-2 ratio ( p = 0.003) were observed in responders. This study highlights the role of angiopoietins in MM which may, thus, be evaluated as potential targets for anti-angiogenic therapy in future.